Enhancing Target Text Comprehension for Lay Audience through Paraphrasing - Muhammad Hendy Anggawijaya; Dimas Adika (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2023)
In translating English into Indonesian, paraphrasing technique is one of the procedures used to translate technical terms so they can be easily comprehended by the target audience. This article aims to highlight the use of paraphrasing in translating a scientific text titled “How Individuals Change Language” with lay audience as the main target. This paper used a qualitative method through analysis of the technique in translating the source text with two versions of translation being provided as steps, namely a default translation and a final one adjusted for the public. Each section provides a discussion of paraphrasing used to simplify the text’s technical terms. This article has received positive reviews from respondents proficient in English. This shows that paraphrasing technique is the best procedure used to translate texts with specific terms so they can be easily understood. This implies that translators of scientific texts with similar audiences may consider paraphrasing as one of the procedures to be used. This is because the procedure can be used to simplify and change various technical terms that are difficult to understand into their more intelligible counterparts.